The learning styles and academic achievements among arts and science streams student - Khalid, Rozalina; Mokhtar, Ahmad Azman; Omar Fauzee, Mohd Sofian; Kasim, Abd Latif; Don, Yahya; Abdussyukur, Nurul Fatni; Ponajan, Fatin Azreen; Mahyuddin, Ahmad; Ghazali, Siti Nor Baya; Rosli, Mohd Hafiz; Soh, Kim Geok (Human Resource Management Academic Research Society, 2013)
This study aims to verify the statement that learning styles influence the academic achievements of students' in the arts and science streams. The main objectives of the study are 1) to seek if students' academic achievement has any significant relationship with their learning styles, 2) to determine the types of learning styles that have significant relationship with students' academic achievement in both the arts and science streams and 3) to determine the demographic factors that have significant relationship to the learning styles among Form 4 and 5 students of both the Arts and Science streams in one of the schools in the northern part of West Malaysia. To measure learning styles, six dimensions from the GRLSS (Grasha-Riechmann Learning Styles Scale) that are free style, avoidance, cooperation, dependent, competition, and participation will be used as the factors. a total of 100 responses were collected through the questionnaire distributed and received one at random which represent 100% response.The data analysis was conducted using SPSS v.19. the data was analysed and interpreted using descriptive and inferential statistics. Findings from the data analysis show that respondents prefer the dependent learning style followed by cooperation in all the variables namely gender, class, ethnic, family income and students' academic achievement. However, there can be a bit of a difference in terms of students who come from the home income of RM 2000, where they prefer cooperation followed by dependency.The Pearson Correlation analysis showed no significant relationship between learning styles as a whole with academic achievements, except for avoidance.The main findings also showed no significant relationship between learning styles and academic achievements. The discussion to findings, implications and suggestions for future researchers will also be presented in this study.